Performance Growth and Development of 15 Genotypes Maize Hybrid at Musi Rawas districts - Rachmad Hersi Martinsyah (Gontor AGROTECH Science Journal, 2019)
Increasing carbohydrate consumption increased as well as increasing population, it essential to increases in the production of through increased productivity by using varieties superior and the widening project of planting. The purpose of this researchis to look at the adaptation of 15 varieties maize hybrid more adaptive Musi Rawas. Using Completely Randomized Block Design with 15 genotypes used was CT16, CT17, CT21, CT22, CT23, CT27, CT29, CT30, CT34, CT37, CT38, CT42, CT46, CT47, CT51. Treatment genotype have significant interaction witht all plants, leaf number, cob long, number of cob seeds, weight of 100 seeds.The appearance of the best hybrid based on growth vegetative are CT17, CT21, CT47.Based on variables cob long, number of cob seeds, and weight of 100 seeds hybrids CT21, CT23, CT51 indicating more adaptive Musi Rawas on land.